Peranan Konselor Dalam Menyampaikan Motivasi Terhadap Siswa Dan Guru - Farhan Imam Razak; Astuti Darmayanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The role of counseling guidance in the creation of an educational environment is dynamic. Individual instruction to change, develop, and enhance behavior. Counselors, in this case BK teachers (guidance and counseling), and guidance and counseling services make efforts to assist students in developing their independence and resolving issues. Students can gain from the guidance and counseling services. The implementation of the function of the guidance and counseling service results in the services, benefits, advantages, or benefits that are obtained from its existence. In this instance, counselors offer assistance with issues that may arise in his life or during the learning process. In the school's education unit, guidance and counseling from BK teachers are very appropriate. The individuals served by counseling and guidance services primarily want to be able to manage their own lives, have their own opinions instead of just following others', adopt their own attitudes, and have the courage to bear the consequences of their actions. The literary method is used in this study to answer all of the questions that will be asked by reading sources that have been filtered and incorporated into a theoretical framework. According to this study, encouragement from the mentor to the supervisor should always be given in a systematic manner to help the student become an independent individual. The general goal of guidance and counseling teachers is to help students grow and develop according to their predispositions, their backgrounds, and the positive demands of their environment. In the meantime, understanding that the general objective is directly related to the difficulties experienced by the students in question, based on their complexity, is the specific objective of guidance and counseling.